2021
DOI: 10.30564/jeisr.v3i2.3722
|View full text |Cite
|
Sign up to set email alerts
|

The Adoption of E-learning by Students in Zimbabwean Universities in the Wake of COVID-19

Abstract: COVID-19 effects have been felt in the education sector worldwide where schools, colleges, and universities were closed as a way to reduce the spread of the deadly pandemic and loss of lives. The Ministry of Higher and Tertiary Education. advocate that no child should be left behind during the COVID-19 era, therefore gave a directive for universities to use other alternative means of teaching and learning to continuously provide teaching and learning to students during the series of lockdown. An efficient eLea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Application of concepts and theory was highly demanded, and past exams papers could not match the new demands. In Zimbabwe online examination were not successful because of the following reasons; non-availability of data (students and lecturers), poor internet connectivity, lack of ICT support and lack of personal electronic gadget [29].…”
Section: Examination Management During Covid-19 Pandemicmentioning
confidence: 99%
See 1 more Smart Citation
“…Application of concepts and theory was highly demanded, and past exams papers could not match the new demands. In Zimbabwe online examination were not successful because of the following reasons; non-availability of data (students and lecturers), poor internet connectivity, lack of ICT support and lack of personal electronic gadget [29].…”
Section: Examination Management During Covid-19 Pandemicmentioning
confidence: 99%
“…Despite efforts by South African universities to run online examinations, literature showed that they were difficult to manage from perspective of student cheating, lack of technological skills by students to upload their answer sheets and lack of support from ICT department [25]. In Zimbabwe, online examination online was at larger extent a failure because of data cost and connectivity [29]. Generally, managing and running examinations online caused a lot of challenges and provided learning curves for most the universities.…”
Section: Sub Question-how Were the Examinations Monitored During This...mentioning
confidence: 99%